ST Segment Depression in the Inferior Leads in Brugada Pattern: A New Sign. Issue 6 (24th December 2014) - Crea, Pasquale; Picciolo, Giuseppe; Luzza, Francesco; Oreto, Giuseppe
Abstract : Background: Brugada pattern (BP) is characterized by J wave and elevated ST segment in the right precordial leads. At times the ECG signs are present only with the electrodes displaced 1 or 2 intercostal spaces above. Methods: We analyzed the electrocardiograms of 87 subjects with type 1 BP looking for ST segment depression (≥ 0.1 mV with duration ≥ 0.08 s) in the inferior leads. In 21 subjects, BP pattern was evident only with V1 –V2 electrodes at the 3rd or 2nd space. Results: ST segment depression was present in 41 cases (47%). In the 21 patients with BP recognizable only at the 2nd or 3rd intercostal space, 10 (48%) presented a significant ST depression in the inferior leads. Conclusions: ST segment analysis in the inferior leads has never been considered for BP diagnosis. When accurately searched for, however, ST segment depression can be observed in those leads in BP, suggesting the need for further investigation.